(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
As seen in the preceding portions, India’s rise during the 1980s does not give an example of Asian state-led growth. Instead, they must be used by the quick availability of new technologies and the qualified personnel. The utilization of these new technologies the technology transfer was largely achieved through improved and cheaper access to imported machines via trade liberalization in the 1980s and early 1990s. Additional technologies that have been key drivers of development since the mid-1990s have improved cellular connection and Internet distribution. In India, a revolution in communication technology cannot have been achieved without the breakdown of state monopolies and the development of competition in the communication business. India would not have taken the fastest-growing industries out of this transition. Obviously, the ongoing progress that we have witnessed since the mid-1990 without the 1991 liberalization measures was not possible. We can recognize that liberalization policies are significant if one thinks that India is still subject to restrictions on enterprise free investment and imports, which were pre-reformed.